Injecting failure: Data center infrastructures and the imaginaries of resilience. Issue 3 (26th May 2020) - Munn, Luke
Abstract: Data center infrastructures provide a lens for understanding the rise of resilience thinking, for grasping the pragmatism and promise of resilience as approach. Unable to anticipate every threat and lockout every contingency, developers of resilient infrastructure "design in" failure, automate monitoring and maintenance, and build capacity to flexibly adapt to new threats. In enacting resilience in the present, they anticipate possible futures, prototyping forms of future life. In this sense, infrastructures should also be understood as operational imaginaries – as systems that powerfully suggest a set of future possibilities by enacting them concretely in the present.